, 24.01.2020tyler9158

# If (x) = 3x + 10x and g(x) = 4x - 2, find (f+ g(x). ο α. 3* + 14x – 2 ο β. 344 6x + 2 ο c. 3x - 6x + 2 ο ο d. 17x- 2 submit

step-by-step explanation:

step-by-step explanation: it is d

what "following statement"?

step-by-step explanation:

(0,-3) see attached graph

step-by-step explanation:

a. to solve the system, graph the two equations.

x = y+3 becomes y=x-3 has m=1/1 and b=-3. start at (0,-3) on the y-axis and plot a point. then move up 1 unit and 1 unit to the right. plot a point and connect.

y=-4x+3 has m =-4/1 and b=-3. start at (0,-3) on the y-axis and plot a point. then move down four units and to the right 1 unit. plot a point and connect.

the solution is the point (x,y) where the two lines intersect. by the graph below it is (0,-3).

b. to solve by substitution, substitute y = -4x-3 into x= y+3

x= (-4x-3) +3

x=-4x

5x=0

x=0

now substitute x = 0 back in to find y.

y= -4(0)-3

y=0-3

y=-3

solution is (0,-3)

c. use elimination by adding the equations together.

x-y=3

4x+y=-3

5x=0

x=0

then substitute into one equation to find y.

y=-4(0)-3

y=-3

Do you know the answer?

### Other questions on the subject: Mathematics

#include<iostream> using namespace std; int** makeMatrix(int n) { int** newM = new int*[n]; for(int i = 0; i < n; i++) { newM[i] = new int[n]; for(int j = 0;j < n; j++)...Read More
Mathematics, 21.06.2019, jace9926
There would be 36.35 pounds...Read More
Mathematics, 21.06.2019, jon3232
Because of mourning president bush's death...Read More